1995
DOI: 10.1046/j.1537-2995.1995.351196110895.x
|View full text |Cite
|
Sign up to set email alerts
|

Low cytokine contamination in buffy coat‐derived platelet concentrates without filtration

Abstract: Platelet concentrates prepared from buffy coats may be virtually free of cytokines (IL-1 beta, IL-6, IL-8, and TNF) during 5 days of storage. Filtration is not required to reduce the recipient's cytokine exposure via such platelet concentrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…It was demonstrated that an accumulation of high levels of cytokines in stored PC can be prevented by leukocyte filtration prior to storage [9, 12], whereas an accumulation of other biological mediators might still be possible [15]. Furthermore, it was observed that leukocyte-derived cytokines are not detectable in PC with a leukocyte contamination below 0.1 × 10 9 [10, 16]. Several groups investigated the risk that passenger PBMC from different individuals in pooled PC generate mixed lymphocyte reactions during storage [17, 18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that an accumulation of high levels of cytokines in stored PC can be prevented by leukocyte filtration prior to storage [9, 12], whereas an accumulation of other biological mediators might still be possible [15]. Furthermore, it was observed that leukocyte-derived cytokines are not detectable in PC with a leukocyte contamination below 0.1 × 10 9 [10, 16]. Several groups investigated the risk that passenger PBMC from different individuals in pooled PC generate mixed lymphocyte reactions during storage [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…The stimulus for cytokine production in PC is still a matter of debate [6, 11, 16]. In our stimulation model, we chose mitogens as they are well characterized and strong cytokine inducers.…”
Section: Discussionmentioning
confidence: 99%
“…Contaminating cytokines, such as TNF-a, IL-1, IL-8 and IL-6, have been described in platelet concentrates prepared from platelet-rich plasma and implicated in transfusion reactions (Muylle et al, 1993;Stack and Snyder, 1994) although thought to be derived from contaminating white blood cells, such as monocytes, and significantly reduced when prefiltered (Muylle and Peetermans, 1994;Aye et al, 1995). A reduction in adverse reactions was also seen when platelet concentrates derived from buffy coats were used (Oksanen et al, 1994), and studies have reported that white cell contamination in such preparations is low and cytokine contamination is rare (Flegel et al, 1995;Kluter et al, 1995).…”
Section: Discusssionmentioning
confidence: 99%
“…55 Leukocyte-reduced PRP prepared by a variety of methods contains undetectable to low concentrations at the limit of detection of ILs and TNF-a, and the concentrations of these molecules does not increase over time. 54,[56][57][58][59][60] These methods of WBC reduction do not affect platelet a-granule release compared to nonleukocyte reduced PRP between 3 and 7 days, although high leukocyte concentration PRP does demonstrate greater platelet activation at the initiation of storage. 58,59 Reported maximum WBC concentrations to prevent inflammatory cytokine accumulation range from 0.1-3 Â 10 3 WBC/mL for all cytokines evaluated and 9.2 Â 10 3 WBC/mL for IL-6.…”
mentioning
confidence: 94%